2013
DOI: 10.2224/sbp.2013.41.9.1519
|View full text |Cite
|
Sign up to set email alerts
|

The Reciprocal Longitudinal Relationship Between the Parent-Adolescent Relationship and Academic Stress in Korea

Abstract: We explored the direction of causation and the longitudinal significance of the relationship between the parent-adolescent relationship and adolescent academic stress. We analyzed responses from the Korean Youth Panel Survey (KYPS), a longitudinal survey that has taken place over 5 years. Just over 2,400 valid responses were analyzed using autoregressive cross-lagged modeling. The results revealed that the parent-adolescent relationship and academic stress experienced by students during 1 year were significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Education is highly valued in Korea, and the expectations of parents, teachers, and students themselves to excel academically can also be a source of intense stress for many students. Therefore, the extreme performance pressure placed on high school students has been subject to criticism (Demircan & Demir, 2014; Kim & Lee, 2013; Oktan, 2014). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Education is highly valued in Korea, and the expectations of parents, teachers, and students themselves to excel academically can also be a source of intense stress for many students. Therefore, the extreme performance pressure placed on high school students has been subject to criticism (Demircan & Demir, 2014; Kim & Lee, 2013; Oktan, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Under strong sociocultural and psychological influences emphasizing the importance of college entrance examinations, Korean adolescents further curtail their sleeping time (Bae & Wickrama, 2015). In addition, the quality and amount of parental involvement and investment in children’s academic performance seem to cause excessive stress for adolescents (Kim & Lee, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…A good parent-child relationship has a significant preventive and interventional effect on the academic pressure of students (Mulyadi et al, 2016). However, the longitudinal study of scholars such as Kim found that the closer the parent-child relationship, the greater the academic pressure of the child (Kim & Lee, 2013). According to the pressure buffer model proposed by Sheldon et al, an excellent social support network can provide people with stable and active support, and sufficient social support resources can strengthen the individual's ability to cope with pressure, thereby preventing individuals from perceiving high levels of pressure (Cohen & Wills, 1985).…”
Section: Questionmentioning
confidence: 99%
“…Secondly, the subjects of the two studies are different. The subjects of Kim et al's study are middle school students who are in their adolescence, who are more emotionally rich and sensitive; with the increase in academic difficulty, when they cannot meet the expectations of their parents or have a gap with their peers, it is easy to have a strong sense of selfblame and guilt, which in turn increases the sense of academic pressure (Kim & Lee, 2013). The object of this study is at the elementary school level, and the academic difficulty is relatively low.…”
Section: The Impact Of Parent-child Relationship On Academic Pressurementioning
confidence: 99%
“…This opinion is supported by Brar (2013) which showed that the secure attachment with parents provides a strong foothold for teenagers in resolving academic conflicts so that they are effectively able to deal with academic pressure. Conversely, if the relationship between teenagers and parents is not good, this will make teenagers suffer more when facing academic stress (Kim & Lee, 2013). In conditions full of academic demands, teenagers may feel alone, confused, and depressed because of the lack of support, warmth, and positive communication with parents.…”
mentioning
confidence: 99%